Rancang bangun sistem informasi geografis pencarian rute terpendek dengan metode ant colony - Pietter, P. Earl; Jusak, Jusak; Tjandrarini, A. B. (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
The diversity of the community in Surabaya can be quite diverse. In addition to the public consists of Surabaya city itself, also consists of non-Surabaya. The Surabaya city communities would require public facilities such as hospitals, bank, or university. Non-residents of Surabaya is not easy to find the desired public facilities, given that non-Surabaya residents do not know the location of public facilities in the city of Surabaya.Existence of the desired public facilities as well as the route to be taken. To support this capability, this system will be developed on Android-based mobile devices for supporting feature Global Positioning System (GPS) and mobile Google Map (mGMap). In order for the location of public facilities as well as the route to be taken by the more accurate method used Ant Colony, Ant Colony method work is by adding pheromone on edge-edge which is the best part of the tour are determined from the start of the algorithm is executed. The advantage of this method is capable of determining the shortest distance to the desired location of public facilities accurately by using more parameters. Some of the most influential parameter is the number of cycles, the number of routes, as well as the number of nodes used.With this system people are expected to know the location of Surabaya public facilities appropriately and accurately. In addition, the system developed along the shortest route to the place of public facilities desired by the user and the shortest alternative route. Keyword: Android, Route, Location, GPS